Identification of important factors that influence the production of lactic acid fermentation by immobilized 'Lactobacillus Delbrueckii' using waste as substrate - Suzana Wahidin; Ani Idris; Hanapi Mat, supervisor; Fakulti Kejuruteraan Kimia dan Kejuruteraan Sumber Asli (2005)
Thesis (Sarjana Kejuruteraan (Bioproses)) - Universiti Teknologi Malaysia, 2005